“Double Indemnity”: um estudo sobre a ficção noir a partir de uma perspectiva intersemiótica - Fontes, Ariani dos Santos (2023)
This dissertation starts from the literary text as a basis for the dialogue between literature and cinema, by presenting, in the light of the assumptions of Jakobson (2000), Ismail Xavier (2003), Susan Bassnett (2003), Julio Plaza (2010) and Linda Hutcheon (2013), a comparative study between literary and cinematographic signs, considering the adaptation process as a creative and autonomous (re)textualization between different media, through the analysis of “Indenização em Dobro”, by James M. Cain, and its adaptation “Pacto de Sangue” (1944), directed by Billy Wilder, whose original titles in English are homonymous – “Double Indeminity”. For this purpose, the text is organized into four chapters, discussing different issues, however, which intertwine to defend the same point of view, namely, noir fiction, as a transgressive cultural phenomenon, which carries at its core the intermediality. To this end, the first chapter provides a brief exposition on the notion of discursive genre (BAKHTIN, 2010; TODOROV, 2018), followed by a theoretical clarification regarding the police genre, starting with its origin, serialized in serials, with Edgar Allan Poe, who founded the enigma school (ALBUQUERQUE, 1979; GUBERN, 1988; BOILEAU-NARCEJAC, 1991; GIARDINELLI, 2013). Therefore, the American noir novel is discussed, as a detective subcategory that emerged in the United States in emotion magazines between the 1920s and 1930s, with crime narratives carried out, at first by hard-boiled detectives such as Samuel Spade, by Dashiell Hammet, and Philip Marlowe, by Raymond Chandler (MANDEL, 1988; SMITH, 2000; SCAGGS, 2005; FONTES, 2012). The second chapter seeks to define the aesthetic-narrative of film noir, considering its classic phase (1941-1958) and its main artistic references, based on studies such as those by A. C. Gomes de Mattos (2001), Fernando Mascarello (2006), Márcia Ortegosa (2010) and Silver and Ursini (2012). Still, in this chapter, there is a short questioning about the archetypes of the femme fatale and the anti-hero, relating them to the concept of type-characters (MASSAUD, 2015) and gender performance (LAURETIS, 1994; KRUTNIK, 2001; KAPLAN, 2012). In the third chapter, some issues involving literature and cinema are presented, conceiving them as already consecrated and legitimized representative forms. Then, the concepts of intersemiotic translation and adaptation are discussed, trying to highlight the impure nature of art itself, based, in 9 particular, for such an approach, on André Bazin (1991), who was a pioneer in defending intermediality, emphasizing the most varied artistic possibilities arising from the dialogue between cinema and the other arts. Thus, finally, there is the analysis of the chosen objects, considering that the film adaptation of a literary text, even if it is of a secondary nature, is a new and independent product, which must be understood as such. In conclusion, it is possible to see that noir fiction safeguards social values of American culture in the first half of the 20th century, as well as establishing an intimate relationship between verbal narrative, noir novel, and filmic narrative, film noir.